Speech Acts in the Discourse of Political Confrontation (on the Material of the British Press in 2004-2005) - Slobodianik, Natalija (Respectus Philologicus, 2006)
The present research investigates the election discourse in Great Britain in 2004-2005 on the basis of speech act theory. The election discourse is the discourse of confrontation by definition as it reflects the position of the sides which both see elections in terms of war. The results of the investigation reveal that the most frequent speech act in this type of discourse is the speech act of evaluation, which is performed not directly (through the use of evaluative words) but through other speech acts which require inference on the part of the listener.
Keywords: political discourse; confrontation; a speech act; a speech strategy; an evaluation